A comparative study of human exposures to household air pollution from commonly used cookstoves in Sri Lanka. (17th February 2016) - Chartier, R.; Phillips, M.; Mosquin, P.; Elledge, M.; Bronstein, K.; Nandasena, S.; Thornburg, V.; Thornburg, J.; Rodes, C.
Abstract: Solid fuel burning cookstoves are a major source of household air pollution (HAP) and a significant environmental health risk in Sri Lanka. We report results of the first field study in Sri Lanka to include direct measurements of both real‐time indoor concentrations and personal exposures of fine particulate matter (PM2.5 ) in households using the two most common stove types in Sri Lanka. A purposive sample of 53 households was selected in the rural community of Kopiwatta in central Sri Lanka, roughly balanced for stove type (traditional or improved 'Anagi') and ventilation (chimney present or absent). At each household, 48‐h continuous real‐time measurements of indoor kitchen PM2.5 and personal (primary cook) PM2.5 concentrations were measured using the RTI MicroPEM ™ personal exposure monitor. Questionnaires were used to collect data related to household demographics, characteristics, and self‐reported health symptoms. All primary cooks were female and of an average age of 47 years, with 66% having completed primary education. Median income was slightly over half the national median monthly income. Use of Anagi stoves was positively associated with a higher education level of the primary cook ( P = 0.026), although not associated with household income ( P = 0.18). The MicroPEM monitors were well‐received by participants, and this study's valid data capture rate exceeded 97%. Participant wearing compliance during waking hours was on average 87.2% on Day 1 and 83.3% on Day 2. Periods of non‐compliance occurred solely during non‐cooking times. The measured median 48‐h average indoor PM2.5 concentration for households with Anagi stoves was 64 μ g/m 3 if a chimney was present and 181 μ g/m 3 if not. For households using traditional stoves, these values were 70 μ g/m 3 if a chimney was present and 371 μ g/m 3 if not. Overall, measured indoor PM2.5 concentrations ranged from a minimum of 33 μ g/m 3 to a maximum of 940 μ g/m 3, while personal exposure concentrations ranged from 34 to 522 μ g/m 3 . Linear mixed effects modeling of the dependence of indoor concentrations on stove type and presence or absence of chimney showed a significant chimney effect (65% reduction; P < 0.001) and an almost significant stove effect (24% reduction; P = 0.054). Primary cooks in households without chimneys were exposed to substantially higher levels of HAP than those in households with chimneys, while exposures in households with traditional stoves were moderately higher than those with improved Anagi stoves. As expected, simultaneously measuring both indoor concentrations and personal exposure levels indicate significant exposure misclassification bias will likely result from the use of a stationary monitor as a proxy for personal exposure. While personal exposure monitoring is more complex and expensive than deploying simple stationary devices, the value an active personal PM monitor like the MicroPEM adds to an exposure study should be considered in future study designs.